PERTUMBUHAN DAN PENERIMAAN PAJAK TERKAIT PENERAPAN PERATURAN PEMERINTAH NOMOR 46 - Dewi, Lidya Kusuma; Putra, Nyoman Wijana (E-Jurnal Akuntansi; Vol 18 No 3 (2017), 2017)
The purpose of this study was to describe the growth of the taxpayer as well as growth in income tax revenue Article 4 Paragraph (2) before and after implementation of Government Regulation No. 46 Year 2013, using the method of documentation. In this study documentation data include data on the growth of SMEs and growth Taxpayers for income tax Article 4 paragraph (2). Research using data analysis techniques parametric analysis techniques using Paired Sample T-Test. Based on the results of the analysis shows: (1) Growth taxpayer SMEs demonstrate the significant value of 0.000 less than 0.05 so that it can concluded there are differences in growth rates before and after the application of PP 46, (2) Growth Tax Article 4, paragraph 2 shows the significant value of 0.001 less than 0.05 so that it can concluded there are differences in growth rates before and after the application of PP 46.
Keywords: PP no. 46 In 2013, The Growth of The Taxpayer, The Growth in Income Tax Revenue Article 4 Paragraph (2)